Office Hysteroscopy: An Insight - Duggal, BS (Med J Armed Forces India, 2002)
In clinical gynaecology, one comes across a large number of patients with intra-uterine pathology. Various investigations have been devised to evaluate these disorders. Hysteroscopy, since its advent has progressed a long way to be recognized as the gold standard in diagnosing intra-uterine pathologies. An attempt to make it an OPD procedure was encouraging. 100 cases of office hysteroscopy were performed at our centre. Pain, patient comfort and acceptability were studied. A favourable outcome was achieved and wider application is recommended.